VD_FINDINFO Jug / 2024 / 26 vom 20. September 2023 - VD Tribunal cantonal (2023)
CONSTATATION DES FAITS, CHANTAGE, FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL | 156 ch. 3 CP, 47 CP, 49 al. 1 CP, 66a al. 1 let. c CP, 10 CPP (CH)